2013
DOI: 10.11648/j.am.20130203.14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Negative Poisson′s Ratio on Stent Applications

Abstract: Abstract:Stents are usually defined as small tubular structures that are inserted into the diseased region which provide mechanical support of damaged artery or some other hollow organ to restore lumen and blood flow conditions in arteries. Recently developed stents may accumulate functions; for example, they can be used for drug delivery or for treatment of bleeding esophageal varices. Further clinical failures such as crushing, removing, restenosis are some of the most serious reasons for continuing stent im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Auxetic materials do exist naturally such as arsenic, cadmium, αcristobalite and many cubic elemental metals (21)(22)(23). Some biological materials are also auxetic including cat skin (24), cow teat skin (25), salamander skin (26) and loadbearing cancellous bone from human shins (27). The arterial endothelium when subjected to both wall shear stresses and a cyclic circumferential strain due to pulsatile blood flow exhibits auxetic effects as well (28).…”
Section: Auxetic Materialsmentioning
confidence: 99%
“…Auxetic materials do exist naturally such as arsenic, cadmium, αcristobalite and many cubic elemental metals (21)(22)(23). Some biological materials are also auxetic including cat skin (24), cow teat skin (25), salamander skin (26) and loadbearing cancellous bone from human shins (27). The arterial endothelium when subjected to both wall shear stresses and a cyclic circumferential strain due to pulsatile blood flow exhibits auxetic effects as well (28).…”
Section: Auxetic Materialsmentioning
confidence: 99%
“…The 2D auxetic materials [2] include honeycombs, graphene, selected laminates, origami, and membranes. Some anisotropic single crystals and lattices are 3D auxetic materials [3,4]. With the unique feature of negative Poisson’s ratio, auxetic materials rise to be a new class of engineering materials, with applications in biomedical devices, aerospace engineering, and automotive engineering [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In tissue engineering, an auxetic scaffold exhibits concurrent axial and transverse expansion or contraction. It has been suggested that, compared to nonauxetic scaffolds, auxetic scaffolds would better integrate with native tissues and/or better promote clinical hard tissue regeneration [18,19].…”
Section: Introductionmentioning
confidence: 99%